2015
DOI: 10.1007/s12223-015-0422-y
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of 1,8-cineole by solid-state fermentation of Eucalyptus waste from the essential oil industry using Pleurotus ostreatus and Favolus tenuiculus

Abstract: Biotechnological conversion of low-cost agro-industrial by-products, such as industrial waste or terpenes from the distillation of essential oils from plants into more valuable oxygenated derivatives, can be achieved by using microbial cells or enzymes. In Argentina, the essential oil industry produces several tons of waste each year that could be used as raw materials in the production of industrially relevant and value-added compounds. In this study, 1,8-cineole, one of the components remaining in the spent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…P. sapidus was cultivated by SSF using rice bran (RB) as substrate and contained in 250 mL flasks as previously described [3,12]. The flasks were prepared by mixing RB (10 g) with water (12 mL).…”
Section: Culture Conditions For Solid-state Fermentationmentioning
confidence: 99%
See 3 more Smart Citations
“…P. sapidus was cultivated by SSF using rice bran (RB) as substrate and contained in 250 mL flasks as previously described [3,12]. The flasks were prepared by mixing RB (10 g) with water (12 mL).…”
Section: Culture Conditions For Solid-state Fermentationmentioning
confidence: 99%
“…Different types of agri-food industry side-streams have been used for SSF to produce enzymes, bioactive compounds, high-quality animal feed supplements, and flavors, among others. Besides, an increasing number of organisms have been used for SSF, like bacteria, yeast, ascomycetes, and basidiomycetes [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparative analysis of production of aroma compounds by Pleurotus ostreatus JMO 95 fruit body and its mycelium obtained under SmF and SSF (agar and sugarcane bagasse) showed that the main aromatic compounds octan-3-one (sweet and fruity odor), octan-3-ol (hazelnut and sweet herbaceous odor) were produced in the same proportions on the agar surface and on the solid support culture. However, in liquid fermentation, the aromatic intensity produced was very low [205].The cultivation of P. ostreatus and Favolus tenuiculus by SSF using eucalyptus waste from the essential oil industry as a substrate was able to transform 1,8-cineole to new aroma compounds which were 1,3,3-trimethyl-2-oxabicyclo[2.2.2]octan-6-ol and 1,3,3-trimethyl-2-oxabicyclo[2.2.2] octan-6-one [206].…”
Section: Aroma Compounds Productionmentioning
confidence: 99%